Pengaruh Content Instagram Marketing, E-Wom, dan E-Service Terhadap Keputusan Pembelian pada Shopee di Samarinda - Andi Indra Kurniawan; Asnawati Asnawati (INDO PUBLISHING, 2026)
This study aims to analyze and explain the Influence of Instagram Marketing Content, E-WOM, and E-Service on Purchasing Decisions at Shopee Samarinda. The independent variables in this study are Instagram Marketing Content, E-WOM, and E-Service. While the dependent variable is Purchasing Decisions. This study was conducted on people who had purchased products at Shopee in Samarinda City consisting of 135 respondents. This study is quantitative. Data collection using a questionnaire by testing the influence of Instagram Marketing Content, E-WOM, and E-Service on Purchasing Decisions at Shopee in Samarinda. Data analysis using the IBM Statistic Product and Service Solution (SPSS) Version 27 program. The results of this study indicate that Instagram Marketing Content, E-WOM, and E-Service have a positive and significant effect on Purchasing Decisions.